National and Sectoral GHG Mitigation Potential A Comparison Across Models - Clapp, Christa (OECD/IEA Climate Change Expert Group Papers, 2009)
Determining comparability of effort between mitigation actions and targets proposed by different countries is an ongoing issue for international climate negotiations. A number of indicators have been proposed to reflect comparability of effort and differences in national circumstances; key amongst these are greenhouse gas (GHG) emissions (per capita), GDP per capita, as well as GHG mitigation potential. This paper focuses on mitigation potential to provide a comparative assessment between six OECD member economies: Australia, Canada, the EU, Japan, Mexico and the US. GHG mitigation potential is defined to be the level of GHG emission reductions that could be realised, relative to the projected emission baseline in a given year, for a given carbon price. Data for the selected countries were obtained across the time horizon of 2005-2050 from a total of 19 models, including models that are used to inform climate policy-makers in each of these economies.